Changing norms to change behavior. [article]. - Miller, Dale T.
Providing people with information about the behavior and attitudes of their peers is a strategy commonly employed by those seeking to reduce behavior deemed harmful either to individuals (e.g., high alcohol consumption). We review norm-based interventions, detailing the logic behind them and the various forms they can take. We give special attention to interventions designed to decrease college students' drinking and increase environment-friendly behaviors. We identify the conditions under which norm information has the highest likelihood of changing the targeted behavior and discuss why this is the case. -- (from the authors)